2013
DOI: 10.1097/adm.0b013e31829da074
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Misuse of Prescription Medication Among Physicians Undergoing Monitoring by a Physician Health Program

Abstract: Objectives Substance related impairment of physicians is a small but serious problem, with significant consequences for patient safety and public health. The purpose of the present study was to identify reasons for prescription drug misuse among physicians referred to a physician health program for monitoring due to substance-related impairment, in order to develop better mechanisms of prevention and intervention. Methods A total of 55 physicians (94.5% male) who were being monitored by their State professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(39 citation statements)
references
References 28 publications
5
31
1
2
Order By: Relevance
“…Of note, amphetamines plus opioids are not recommended clinically. Other possible explanations as to why these medications are misused are to mitigate symptoms of substance withdrawal or reduce core symptoms, dampen other adverse effects of drugs of abuse, or to self‐medicate comorbid undiagnosed psychopathology or traits . Further research highlighting both the prevalence and etiologies of prescription medication misuse in these populations is necessary, particularly given the high risk of overdose and increasing concerns about adjunct psychotropic medications.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, amphetamines plus opioids are not recommended clinically. Other possible explanations as to why these medications are misused are to mitigate symptoms of substance withdrawal or reduce core symptoms, dampen other adverse effects of drugs of abuse, or to self‐medicate comorbid undiagnosed psychopathology or traits . Further research highlighting both the prevalence and etiologies of prescription medication misuse in these populations is necessary, particularly given the high risk of overdose and increasing concerns about adjunct psychotropic medications.…”
Section: Discussionmentioning
confidence: 99%
“…In the largest longitudinal study on this topic to date, analysis of data from over 34,000 adult participants in Waves 1 and 2 of the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) revealed that baseline mood disorders and anxiety disorders significantly predicted the incidence of nonmedical opioid use and opioid dependence several years later (Martins et al, 2012). Complementing these findings, qualitative research indicates that self-medication of emotional pain is a leading reason for nonmedical use of and dependence on prescription opioids (Merlo et al, 2013). …”
mentioning
confidence: 99%
“…Physicians fulfil a special and very powerful role as health experts and they can self-prescribe and self-treat their conditions (Rosvold et al 1998;Cicala 2003;Wallace et al 2009). Accordingly, physicians were found to be more likely than other members of the general public to have prescription drug use disorders (Merlo et al 2013). Additionally, physicians carry the responsibility for patients' health.…”
Section: Introductionmentioning
confidence: 99%
“…This means that the study is limited in the sense that it does not direct much attention to the implications of family relations affecting substance use disorders. I leave the analysis of private and personal factors affecting SUD to others (see, for example, (Merlo et al 2013)). There may be a selection bias among the self-selected participants; they may represent a particular kind of physician, who is interested in sharing his/her experiences in order to help colleagues.…”
Section: Medical Socialisation Self-medication and Social Technologiesmentioning
confidence: 99%